Simple In-Hospital Interventions to Reduce Door-to-CT Time in Acute Stroke. (10th July 2016) - Sadeghi-Hokmabadi, Elyar; Taheraghdam, Aliakbar; Hashemilar, Mazyar; Rikhtegar, Reza; Mehrvar, Kaveh; Mehrara, Mehrdad; Mirnour, Reshad; Hassasi, Rogayyeh; Aliyar, Hannane; Farzi, Mohammadamin; Hasaneh Tamar, Somayyeh
Abstract : Background . Intravenous tissue plasminogen activator, a time dependent therapy, can reduce the morbidity and mortality of acute ischemic stroke. This study was designed to assess the effect of simple in-hospital interventions on reducing door-to-CT (DTC) time and reaching door-to-needle (DTN) time of less than 60 minutes. Methods . Before any intervention, DTC time was recorded for 213 patients over a one-year period at our center. Five simple quality-improvement interventions were implemented, namely, call notification, prioritizing patients for CT scan, prioritizing patients for lab analysis, specifying a bed for acute stroke patients, and staff education. After intervention, over a course of 44 months, DTC time was recorded for 276 patients with the stroke code. Furthermore DTN time was recorded for 106 patients who were treated with IV thrombolytic therapy. Results . The median DTC time significantly decreased in the postintervention period comparing to the preintervention period [median (IQR); 20 (12–30) versus 75 (52.5–105), P < 0.001 ]. At the postintervention period, the median (IQR) DTN time was 55 (40–73) minutes and proportion of patients with DTN time less than 60 minutes was 62.4% (P < 0.001 ). Conclusion . Our interventions significantly reduced DTC time and resulted in an acceptable DTN time. These interventions are feasible in most hospitals and should be considered.